The Three-Tier Test Approach to Measuring Misconceptions in High School Physics: Focus on Work and Energy - Aini, Anggun Nur; Untoro, Nur (Impulse: Journal of Research and Innovation in Physics Education, 2025)
This study aims to identify misconceptions experienced 10th grade students on the subject of Work and Energy using a three-tier test. The type of research used is quantitative descriptive. The data collection instrument was a three-tier test consisting of 10 questions, which had been tested and found to have a validity of 0.96 and reliability (Cronbach's Alpha) of 0.81, making it suitable for measuring students' conceptual understanding. There were 34 students in this study, with purposive sampling used as the sampling technique. The data were obtained through Google Forms and analyzed statistically to identify the level of students' misconceptions. The results showed that the highest misconception occurred in the subconcept of work (79.41%), followed by kinetic energy and potential energy (55.88%), and the law of conservation of energy (41.18%). These findings are expected to provide insight for educators and curriculum developers in designing more effective learning strategies, thereby helping students overcome misconceptions and improve their understanding of physics concepts. Thus, it can be concluded that most students still have misconceptions about the concepts of Work and Energy, requiring learning strategies that emphasize strengthening conceptual understanding.